On the Half-Heusler compounds Nb1-xTi, Zr, HfxFeSb: Phase relations, thermoelectric properties at low and high temperature, and mechanical properties. (15th August 2017) - Tavassoli, A.; Failamani, F.; Grytsiv, A.; Rogl, G.; Heinrich, P.; Müller, H.; Bauer, E.; Zehetbauer, M.; Rogl, P.
Abstract: A re-investigation of phase equilibria, crystal structure and homogeneity region of the Half-Heusler (HH) phase in the ternary system Nb-Fe-Sb at 600 °C has solved controversies in the literature confirming the version of Melnyk et al. ([1] J. Phase Equilibria 20 (2) (1999) 113–118). For the first time transport properties of Half-Heusler (HH) compounds NbFeSb and Nb0.85 M0.15 FeSb (M = Ti, Zr, Hf) were studied in the full temperature range from 4.2 to 823 K. The semiconducting material NbFeSb has an electronic structure close to a metal-to-insulator transition, which leads to changes of the conductivity type with the composition as well as with increasing temperature. Ti, Zr and Hf doped NbFeSb alloys show metallic behavior and were confirmed to be high ZT p-type thermoelectric materials. Surprisingly, the lattice thermal conductivity for the Zr-doped composition was found to be higher than those of the Ti- and Hf doped materials; this effect can be explained in terms of mass and strain field fluctuations. For the first time we report experimental information on thermal expansion coefficients, specific heat and elastic moduli for these p-type compounds. The mechanical properties show a good compatibility with those previously reported for n-type HH alloys. Graphical abstract: Image